Annual Danish language essay competition - Ivanov, Yoan; Vaseva, Gergana; Bineva, Aglaja (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2024)
Since 2015, the Hans Christian Andersen Centre for Research and Information at Sofia University St. Kliment Ohridski in collaboration with the Embassy of Denmark in Sofia and the Danish Agency for Culture and Palaces (Slots- og Kulturstyrelsen), has organised the Annual Danish Language Essay Competition.